2020
DOI: 10.1111/anec.12809
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between apnea–hypopnea index and Tp‐Te interval, Tp‐Te/QT, and Tp‐Te/QTc ratios in obstructive sleep apnea

Abstract: Background Obstructive sleep apnea (OSA) is a highly prevalent sleep disorder associated with important cardiovascular complications including ventricular arrhythmias. Tp‐Te interval, Tp‐Te/QT, and Tp‐Te/QTc ratios are repolarization indices representing ventricular arrhythmogenic potential. These parameters are associated with ventricular arrhythmias and sudden cardiac death. The aim of this study was to investigate the correlation between apnea–hypopnea index and Tp‐Te, Tp‐Te/QT, and Tp‐Te/QTc in OSA. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Baumert et al 24 showed that OSAS is associated with changes in QT interval variability during sleep. Sökmen et al 25 , Kilicarlan et al 26 , and Karacop et al 27 found that Tp-e, Tpe/QT ratio, and Tp-e/ QTc ratio were prolonged in OSAS patients. In our study, QT and QTc intervals were not different between the study and control groups.…”
Section: Discussionmentioning
confidence: 99%
“…Baumert et al 24 showed that OSAS is associated with changes in QT interval variability during sleep. Sökmen et al 25 , Kilicarlan et al 26 , and Karacop et al 27 found that Tp-e, Tpe/QT ratio, and Tp-e/ QTc ratio were prolonged in OSAS patients. In our study, QT and QTc intervals were not different between the study and control groups.…”
Section: Discussionmentioning
confidence: 99%